A Permission Document (Icazetname) belonging to the Ocak of Koçu Baba - Sakarlı, Nazmiye (Journal of Alevism-Bektashism Studies, 2022)
Seyit Hasan Gazi, one of the erens (sacred persons) who came to Anatolia with Haci Bektash Veli in the 13th century, is also known as Koçu Baba. According to the information in the sources of Vilayetname, he is the father of Abdal Musa and Mehmed Abdal. At the same time, through his father Seyit Haydar Gazi, who is the uncle of Haci Bektashi Veli, he is related to him. It is accepted that these velis (sacred persons) are connected to the Prophet Muhammed through the lineage of Ibrahim Mükerrem Mücab, the son of the seventh Imam Musa Kazim, who is their ancestor, and therefore have the characteristics of seyyid. Today, the sacred site of Koçu Baba is in the Koçubaba village, located in the Balişeyh district of Kirikkale. The structure based on the devotion to the Truth, which is maintained by the seyyids in the ocak of Koçu Baba, one of the Anatolian Alevi ocaks, and in the other ocaks, is extremely important within the Alevi-Bektashi belief system. Thereby it is known that seyyids elected for the dede position with the approval of the guides to whom the ocak is affiliated, serve as dede with the “approval, permission documents” called icazetname. The document analysed in our study is an icazetname that belongs to the Koçu Baba ocak. According to the Alevi-Bektashi researches, it appears that the icazetname tradition, which is thought to have started in the 11th century, was passed on by the guide ocak to the ocaks affiliated to it. The type of icazetname is also important in terms of the rank of the dede, selected as a guide during his period, and determining which ocak the guides were affiliated with. Information about the fact that the ocak of Koçu Baba is affiliated with the dergah of Haci Bektashi Veli and that it maintains the tradition of receiving icazet documents from this dergah, is important as an indicator of the hierarchy between ocaks. The connection of the dede system, usually thought to be passed on from father to son, with the past also appears in another example. Icazetname in question is an important document for us to understand the character of the period because it was written in Ottoman Turkish in the 19th century in a clear and understandable language.